In silico docking and molecular dynamics for the discovery of inhibitors of enteric methane production in ruminants — A review - Kamburawala Kankanamge Tharindu Namal Ranaweera; Myunggi Baik (Animal Bioscience)
The increase in methane emissions, a major greenhouse gas, threatens human well-being and global ecosystems due to its contribution to global warming. Livestock, particularly ruminants, have been a major research topic in recent decades due to their methane production. Therefore, the objective of the current review was to comprehensively discuss the in silico techniques used to mitigate methane production from ruminants. The review covers the principles of in silico docking and molecular dynamics, which can be used to develop methanogenesis inhibitors. It also discusses specific methanogen enzymes as potential targets for inhibitor development. Furthermore, in silico-based methanogenesis inhibitor development studies have been reviewed with the authors’ opinions. The further use of in silico-based research techniques, including artificial intelligence-based systems, is encouraged to help reduce methane production from livestock more efficiently and cost-effectively.